2020
DOI: 10.3390/ijms21207748
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Pseudomonas aeruginosa PAO1 to UV-activated Titanium Dioxide/Silica Nanotubes

Abstract: Pseudomonas aeruginosa is a bacterium of high clinical and biotechnological importance thanks to its high adaptability to environmental conditions. The increasing incidence of antibiotic-resistant strains has created a need for alternative methods to increase the chance of recovery in infected patients. Various nanomaterials have the potential to be used for this purpose. Therefore, we aimed to study the physiological response of P. aeruginosa PAO1 to titanium dioxide/silica nanotubes. The results suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 49 publications
(69 reference statements)
2
9
0
Order By: Relevance
“…4, in the population's growth curve co-incubated with TiO 2 . It was the probable cause for the delay in entering the logarithmic growth phase, similarly to phenomena described for silica nanotubes (Augustyniak et al 2020a).…”
Section: Biofilm Formationmentioning
confidence: 60%
See 2 more Smart Citations
“…4, in the population's growth curve co-incubated with TiO 2 . It was the probable cause for the delay in entering the logarithmic growth phase, similarly to phenomena described for silica nanotubes (Augustyniak et al 2020a).…”
Section: Biofilm Formationmentioning
confidence: 60%
“…However, if these agglomerates have not been firmly attached to the forming biofilm, they could be washed out during the staining procedure (Merritt et al 2015). The agglomeration of pseudomonads promoted by nanomaterials has been previously described for carbon nanotubes and silica nanotubes (Ma et al 2010;Augustyniak et al 2020a). In the current studies, signs of such aggregation can be found in Fig.…”
Section: Biofilm Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation for this result could be that UV exposure might trigger strong agglomeration of P . aeruginosa (Augustyniak et al, 2020), leading to cells being less susceptible than E . coli to the UV doses applied.…”
Section: Discussionmentioning
confidence: 99%
“…The disruption of microbiota can influence cause, e.g., interruptions in the cycles of elements (sulfur, phosphorus, nitrogen, and carbon) (Philippot et al 2013). On the other hand, nanomaterials' admixtures may be used to change microorganisms' behavior that should be further studied to use these phenomena in applied sciences (e.g., biotechnology) (Augustyniak et al 2016(Augustyniak et al , 2020a.…”
Section: Introductionmentioning
confidence: 99%